RANCANG BANGUN ELECTRICWHEELCHAIR CONTROLLED BY ANDROID DEVICE WITH SPEECH RECOGNITION COMMANDS FUNCTION - Pradana, Angga; Hidayat, Ferry; Taksiono, Muhammad Agus; Winarto, Muhammad Faisal; Hatta, Liem Yuliana Katina (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Conventional wheelchair is not unable to allow users make free move. Meanwhile, electronic wheelchair allows user to move without assistance but the hand-base disable people are unable to move the chair given they have problem in using joystick. The use voice as moving order is offered. Android Smartphone is chosen due to the availability of open source operating system with speech recognition of multi-language. Android Wheelchair can be used through voice order âstraightâ, âbackwardâ, ârightâ, âleftâ. The voice order is synchronized with the list provided in the database. If the voice is matched, the android smartphone will send order to microcontroller through wireless communication and will move the wheelchair.The experiment showed that from six times order through voice, those six orders were recognized by smartphone Android and it move to the direction mentioned previously. The wheelchair has been equipped with ultrasonic sensor to recognize surrounding environment so to avoid any possibility of crash.